RELATION OF RELIGION, ECONOMY AND POLITICS: Islamization of Malay Community through Trade and Kingdom - Sudarman Sudarman; Mohammad Hidayaturrahman (AL-TAHRIR, 2020)
Abstract: Some scholars have suggested a paradigm that the process of conversion to Islam in the Malay community was spread by Sufis. Historical reconstruction in this region is always associated with the teachings, rituals and religious behavior of Sufis. This research was conducted to describe the process of conversion to Islam in three paradigms, namely, political economy, history, and religion. This study found that the conversion of religion in Malay society was mostly played by economic actors. To facilitate this conversion, economic agents married local women and negotiated with the ruling sultans. From the existing sources (manuscripts and archives), economic actors had a significant role in Islam conversion for Malay society. Economic actors, in the 17-18 century AD, consisting of traders, were connected with countries in the Indian Ocean. Some of them came to the West Coast of Sumatra to trade spices. The traders who came were Muslims. Their arrival brought two purposes at once, namely the teachings of religion in the right hand and trading commodities in the left hand. Both of these goals were the driving force of traders to spread Islam in every visited region. This study has proven correlative with the condition of the Islamic community in the current Malay community, which is more engaged in the trade than other sectors. At the same time, the community becomes devout Muslims.الملخص: اقترح بعض الباحثين أن التحويل المتكامل إلى الدين الإسلامى فى المجتمع الملاوى نتيجة من جهود المتصوفين الكتابة التاريخية عن هذه المنطقة دائما  متعلقة بالتعاليم، الطقوس، والأنشطة الدينية لهذه الفرقة يحاول هذا البحث تصوير وتفصيل عملية التحويل إلى الدين الإسلامى فى المجتمع الملاوى من جهة ثلاث: السياسى والاقتصادى، التاريخى، والدينى حصل البحث إلى النتيجة التالية أن العامل الاقتصادى له دور أهم فى التحويل الدينى فى المجتمع الملاوى تسهيلا لهذا التحويل، التجار يتزوجون المواطنات ويتفاوضون الملوك يمكن إدراك هذا الرأى من الأرشيف والمخطوطات لدينا كان التجار فى القرنى السابع والثامن عشر الميلادى مترابطين مع أنهم منتشرون عبر المحيط الهندى. عدد منهم ، معظمهم مسلمون، زار الساحل الغربى لسومطرة لتجارة التوابل والدعوة الإسلامية. هما، التجارة والدعوة، عاملان رئيسيان فى نشاطهم الاقتصادى والدينى كانت نتيجة هذا البحث توافق بأحوال المجتمع الملاوى فى زماننا الحاضر الذى يشتغل بالتجارة أكثر من اشتغالهم فى المهن الأخرى، بالاضافة إلى كونهم مسلمين متدينينAbstrak: Sebagian kalangan, selama ini membangun paradigma, bahwa proses konversi ke agama Islam pada masyarakat Melayu disebarkan oleh para sufi. Rekonstruksi sejarah di wilayah ini selalu dikaitkan dengan ajaran, ritual dan perilaku keagamaan para sufi. Penelitian ini dilakukan untuk menggambarkan dan mendeskripsikan proses konversi ke agama Islam dalam tiga paradigma, ekonomi politik, sejarah, dan keagamaan. Penelitian ini menemukan bahwa konversi agama pada masyarakat Melayu lebih banyak diperankan oleh aktor ekonomi. Untuk mempermudah konversi tersebut, para pelaku ekonomi menikahi wanita setempat, dan melakukan negosiasi dengan sultan yang berkuasa. Dari sumber yang ada (manuskrip dan arsip), para pelaku ekonomi memiliki peran signifikan dalam mengkonversi agama Islam pada masyarakat Melayu. Aktor ekonomi, pada abad ke 17-18 masehi, yang terdiri dari para pedagang terkoneksi dengan negeri-negeri yang ada di Samudra Hindia. Sebagian dari mereka datang ke Pantai Barat, Sumatera untuk berdagang rempah-rempah. Para pedagang yang datang tersebut adalah pemeluk agama Islam. Kedatangan mereka membawa dua tujuan sekaligus, ajaran agama di tangan kanan dan komoditas perdagangan di tangan kiri. Kedua tujuan tersebut yang menjadi daya penggerak para pedagang untuk menyebarkan Islam di setiap wilayah yang disinggahi. Penelitian ini berkorelasi dengan kondisi masyarakat Islam pada masyarakat Melayu saat ini, yang lebih banyak menekuni sektor perdagangan dibanding sektor lain. Pada saat yang sama juga menjadi pemeluk Islam yang taat.